Ablation of the inferior olive prevents H-reflex down-conditioning in rats. - Xiang Yang Chen; Wang, Yu; Yi Chen; Chen, Lu; Jonathan Wolpaw (Journal of neurophysiology, 2016)
We evaluated the role of the inferior olive (IO) in acquisition of the spinal cord plasticity that underlies H-reflex down-conditioning, a simple motor skill. The IO was chemically ablated before a 50-day exposure to an operant conditioning protocol that rewarded a smaller soleus H-reflex. In normal rats, down-conditioning succeeds (i.e., H-reflex size decreases at least 20%) in 80% of animals. Down-conditioning failed in every IO-ablated rat (P< 0.001 vs. normal rats). IO ablation itself had no long-term effect on H-reflex size. These results indicate that the IO is essential for acquisition of a down-conditioned H-reflex. With previous data, they support the hypothesis that IO and cortical inputs to cerebellum enable the cerebellum to guide sensorimotor cortex plasticity that produces and maintains the spinal cord plasticity that underlies the down-conditioned H-reflex. They help to further define H-reflex conditioning as a model for understanding motor learning and as a new approach to enhancing functional recovery after trauma or disease.
Keywords: Spinal Cord

Electrocorticographic activity over sensorimotor cortex and motor function in awake behaving rats. - Chadwick B. Boulay; Xiang Yang Chen; Jonathan Wolpaw (J Neurophysiol, 2015)
Sensorimotor cortex exerts both short-term and long-term control over the spinal reflex pathways that serve motor behaviors. Better understanding of this control could offer new possibilities for restoring function after central nervous system trauma or disease. We examined the impact of ongoing sensorimotor cortex (SMC) activity on the largely monosynaptic pathway of the H-reflex, the electrical analog of the spinal stretch reflex. In 41 awake adult rats, we measured soleus electromyographic (EMG) activity, the soleus H-reflex, and electrocorticographic activity over the contralateral SMC while rats were producing steady-state soleus EMG activity. Principal component analysis of electrocorticographic frequency spectra before H-reflex elicitation consistently revealed three frequency bands: μβ (5-30 Hz), low γ (γ1; 40-85 Hz), and high γ (γ2; 100-200 Hz). Ongoing (i.e., background) soleus EMG amplitude correlated negatively with μβ power and positively with γ1 power. In contrast, H-reflex size correlated positively with μβ power and negatively with γ1 power, but only when background soleus EMG amplitude was included in the linear model. These results support the hypothesis that increased SMC activation (indicated by decrease in μβ power and/or increase in γ1 power) simultaneously potentiates the H-reflex by exciting spinal motoneurons and suppresses it by decreasing the efficacy of the afferent input. They may help guide the development of new rehabilitation methods and of brain-computer interfaces that use SMC activity as a substitute for lost or impaired motor outputs.
Keywords: brain-computer interface; cortex; H-Reflex; Motor control; Spinal Cord

Soleus H-reflex operant conditioning changes the H-reflex recruitment curve. - Thompson, Aiko K.; Xiang Yang Chen; Jonathan Wolpaw (Muscle & nerve, 2013)
INTRODUCTION: Operant conditioning can gradually change the human soleus H-reflex. The protocol conditions the reflex near M-wave threshold. In this study we examine its impact on the reflexes at other stimulus strengths. METHODS: H-reflex recruitment curves were obtained before and after a 24-session exposure to an up-conditioning (HRup) or a down-conditioning (HRdown) protocol and were compared. RESULTS: In both HRup and HRdown subjects, conditioning affected the entire H-reflex recruitment curve. In 5 of 6 HRup and 3 of 6 HRdown subjects, conditioning elevated (HRup) or depressed (HRdown), respectively, the entire curve. In the other HRup subject or the other 3 HRdown subjects, the curve was shifted to the left or to the right, respectively. CONCLUSIONS: H-reflex conditioning does not simply change the H-reflex to a stimulus of particular strength; it also changes the H-reflexes to stimuli of different strengths. Thus, it is likely to affect many actions in which this pathway participates.
Keywords: motor learning; plasticity; Rehabilitation; Spinal Cord

Cortical stimulation causes long-term changes in H-reflexes and spinal motoneuron GABA receptors. - Wang, Yu; Yi Chen; Lu Chen; Jonathan Wolpaw; Xiang Yang Chen (Journal of neurophysiology, 2012)
The cortex gradually modifies the spinal cord during development, throughout later life, and in response to trauma or disease. The mechanisms of this essential function are not well understood. In this study, weak electrical stimulation of rat sensorimotor cortex increased the soleus H-reflex, increased the numbers and sizes of GABAergic spinal interneurons and GABAergic terminals on soleus motoneurons, and decreased GABA(A) and GABA(B) receptor labeling in these motoneurons. Several months after the stimulation ended the interneuron and terminal increases had disappeared, but the H-reflex increase and the receptor decreases remained. The changes in GABAergic terminals and GABA(B) receptors accurately predicted the changes in H-reflex size. The results reveal a new long-term dimension to cortical-spinal interactions and raise new therapeutic possibilities.
Keywords: Spinal Cord

H-reflex up-conditioning encourages recovery of EMG activity and H-reflexes after sciatic nerve transection and repair in rats. - Yi Chen; Wang, Yu; Lu Chen; Sun, Chenyou; English, Arthur W.; Jonathan Wolpaw; Xiang Yang Chen (The Journal of neuroscience : the official journal of the Society for Neuroscience, 2010)
Operant conditioning of the spinal stretch reflex or its electrical analog, the H-reflex, produces spinal cord plasticity and can thereby affect motoneuron responses to primary afferent input. To explore whether this conditioning can affect the functional outcome after peripheral nerve injury, we assessed the effect of up-conditioning soleus (SOL) H-reflex on SOL and tibialis anterior (TA) function after sciatic nerve transection and repair. Sprague Dawley rats were implanted with EMG electrodes in SOL and TA and stimulating cuffs on the posterior tibial nerve. After control data collection, the sciatic nerve was transected and repaired and the rat was exposed for 120 d to continued control data collection (TC rats) or SOL H-reflex up-conditioning (TU rats). At the end of data collection, motoneurons that had reinnervated SOL and TA were labeled retrogradely. Putative primary afferent terminals [i.e., terminals containing vesicular glutamate transporter-1 (VGLUT1)] on SOL motoneurons were studied immunohistochemically. SOL (and probably TA) background EMG activity recovered faster in TU rats than in TC rats, and the final recovered SOL H-reflex was significantly larger in TU than in TC rats. TU and TC rats had significantly fewer labeled motoneurons and higher proportions of double-labeled motoneurons than untransected rats. VGLUT1 terminals were significantly more numerous on SOL motoneurons of TU than TC rats. Combined with the larger H-reflexes in TU rats, this anatomical finding supports the hypothesis that SOL H-reflex up-conditioning strengthened primary afferent reinnervation of SOL motoneurons. These results suggest that H-reflex up-conditioning may improve functional recovery after nerve injury and repair.
Keywords: conditioning; peripheral nerve; plasticity; Reflex; regeneration; Spinal Cord

Acquisition of a simple motor skill: task-dependent adaptation plus long-term change in the human soleus H-reflex. - Thompson, Aiko K.; Xiang Yang Chen; Jonathan Wolpaw (The Journal of neuroscience : the official journal of the Society for Neuroscience, 2009)
Activity-dependent plasticity occurs throughout the CNS. However, investigations of skill acquisition usually focus on cortex. To expand the focus, we analyzed in humans the development of operantly conditioned H-reflex change, a simple motor skill that develops gradually and involves plasticity in both the brain and the spinal cord. Each person completed 6 baseline and 24 conditioning sessions over 10 weeks. In each conditioning session, the soleus H-reflex was measured while the subject was or was not asked to increase (HRup subjects) or decrease (HRdown subjects) it. When the subject was asked to change H-reflex size, immediate visual feedback indicated whether a size criterion had been satisfied. Over the 24 conditioning sessions, H-reflex size gradually increased in six of eight HRup subjects and decreased in eight of nine HRdown subjects, resulting in final sizes of 140 +/- 12 and 69 +/- 6% of baseline size, respectively. The final H-reflex change was the sum of within-session (i.e., task-dependent) adaptation and across-session (i.e., long-term) change. Task-dependent adaptation appeared within four to six sessions and persisted thereafter, averaging +13% in HRup subjects and -15% in HRdown subjects. In contrast, long-term change began after 10 sessions and increased gradually thereafter, reaching +27% in HRup subjects and -16% in HRdown subjects. Thus, the acquisition of H-reflex conditioning consists of two phenomena, task-dependent adaptation and long-term change, that together constitute the new motor skill. In combination with previous data, this new finding further elucidates the interaction of plasticity in brain and spinal cord that underlies the acquisition and maintenance of motor skills.
Keywords: H-Reflex; motor learning; motor skill; operant conditioning; plasticity; Spinal Cord

H-reflex down-conditioning greatly increases the number of identifiable GABAergic interneurons in rat ventral horn. - Wang, Yu; Pillai, Shreejith; Jonathan Wolpaw; Xiang Yang Chen (Neuroscience letters, 2009)
H-reflex down-conditioning increases GABAergic terminals on spinal cord motoneurons. To explore the origins of these terminals, we studied the numbers and distributions of spinal cord GABAergic interneurons. The number of identifiable GABAergic interneurons in the ventral horn was 78% greater in rats in which down-conditioning was successful than in naive rats or rats in which down-conditioning failed. No increase occurred in other spinal lamina or on the contralateral side. This finding supports the hypothesis that the corticospinal tract influence that induces the motoneuron plasticity underlying down-conditioning reaches the motoneuron through GABAergic interneurons in the ventral horn.
Keywords: activity-dependent plasticity; GABAergic interneurons; H-reflex conditioning; learning and memory; Motor control; Spinal Cord

Effects of H-reflex up-conditioning on GABAergic terminals on rat soleus motoneurons. - Pillai, Shreejith; Wang, Yu; Jonathan Wolpaw; Xiang Yang Chen (The European journal of neuroscience, 2008)
To explore the role of spinal cord plasticity in motor learning, we evaluated the effects of H-reflex operant conditioning on GABAergic input to rat spinal motoneurons. Previous work indicated that down-conditioning of soleus H-reflex increases GABAergic input to soleus motoneurons. This study explored the effect of H-reflex up-conditioning on GABAergic input. Of nine rats exposed to H-reflex up-conditioning, up-conditioning was successful (H-reflex increase >or= 20%) in seven and failed (change < 20%) in two. These rats and eight naive control (i.e. unconditioned) rats were injected with cholera toxin subunit B-conjugated Alexa fluor 488 into the soleus muscle to retrogradely label soleus motoneurons. Sections containing soleus motoneurons were processed for GAD(67) [one of the two principal forms of the GABA-synthesizing enzyme glutamic acid decarboxylase (GAD)] with an ABC-peroxidase system. Two blinded independent raters counted and measured GABAergic terminals on these motoneurons. Unlike successful down-conditioning, which greatly increased the number of identifiable GABAergic terminals on the motoneurons, up-conditioning did not significantly change GABAergic terminal number. Successful up-conditioning did produce slight but statistically significant increases in GABAergic terminal diameter and soma coverage. These results are consistent with other data indicating that up- and down-conditioning are not mirror images of each other, but rather have different mechanisms. Although the marked changes in GABAergic terminals with down-conditioning probably contribute to H-reflex decrease, the modest changes in GABAergic terminals associated with up-conditioning may be compensatory or reactive plasticity, rather than the plasticity responsible for H-reflex increase. As a variety of spinal and supraspinal GABAergic neurons innervate motoneurons, the changes found with up-conditioning may be in terminals other than those affected in successful down-conditioning.
Keywords: activity-dependent plasticity; Learning; Memory; Motor control; Spinal Cord

The cerebellum in maintenance of a motor skill: a hierarchy of brain and spinal cord plasticity underlies H-reflex conditioning. - Jonathan Wolpaw; Xiang Yang Chen (Learning & memory (Cold Spring Harbor, N.Y.), 2006)
Operant conditioning of the H-reflex, the electrical analog of the spinal stretch reflex, is a simple model of skill acquisition and involves plasticity in the spinal cord. Previous work showed that the cerebellum is essential for down-conditioning the H-reflex. This study asks whether the cerebellum is also essential for maintaining down-conditioning. After rats decreased the soleus H-reflex over 50 d in response to the down-conditioning protocol, the cerebellar output nuclei dentate and interpositus (DIN) were ablated, and down-conditioning continued for 50-100 more days. In naive (i.e., unconditioned) rats, DIN ablation itself has no significant long-term effect on H-reflex size. During down-conditioning prior to DIN ablation, eight Sprague-Dawley rats decreased the H-reflex to 57% (+/-4 SEM) of control. It rose after ablation, stabilizing within 2 d at about 75% and remaining there until approximately 40 d after ablation. It then rose to approximately 130%, where it remained through the end of study 100 d after ablation. Thus, DIN ablation in down-conditioned rats caused an immediate increase and a delayed increase in the H-reflex. The final result was an H-reflex significantly larger than that prior to down-conditioning. Combined with previous work, these remarkable results suggest that the spinal cord plasticity directly responsible for down-conditioning, which survives only 5-10 d on its own, is maintained by supraspinal plasticity that survives approximately 40 d after loss of cerebellar output. Thus, H-reflex conditioning seems to depend on a hierarchy of brain and spinal cord plasticity to which the cerebellum makes an essential contribution.
Keywords: Spinal Cord

Diurnal H-reflex variation in mice. - Jonathan S. Carp; Tennissen, Ann M.; Xiang Yang Chen; Jonathan Wolpaw (Experimental brain research. Experimentelle Hirnforschung. Expérimentation cérébrale, 2006)
Mice exhibit diurnal variation in complex motor behaviors, but little is known about diurnal variation in simple spinally mediated functions. This study describes diurnal variation in the H-reflex (HR), a wholly spinal and largely monosynaptic reflex. Six mice were implanted with tibial nerve cuff electrodes and electrodes in the soleus and gastrocnemius muscles, for recording of ongoing and nerve-evoked electromyographic activity (EMG). Stimulation and recording were under computer control 24 h/day. During a 10-day recording period, HR amplitude varied throughout the day, usually being larger in the dark than in the light. This diurnal HR variation could not be attributed solely to differences in the net ongoing level of descending and segmental excitation to the spinal cord or stimulus intensity. HRs were larger in the dark than in the light even after restricting the evoked responses to subsets of trials having similar ongoing EMG and M-responses. The diurnal variation in the HR was out of phase with that reported previously for rats, but was in phase with that observed in monkeys. These data, supported by those in other species, suggest that the supraspinal control of the excitability of the HR pathway varies throughout the day in a species-specific pattern. This variation should be taken into account in experimental and clinical studies of spinal reflexes recorded at different times of day.
Keywords: circadian rhythm; Electromyography; implanted electrodes; Monosynaptic; Reflex; Spinal Cord

H-reflex operant conditioning in mice. - Jonathan S. Carp; Tennissen, Ann M.; Xiang Yang Chen; Jonathan Wolpaw (Journal of neurophysiology, 2006)
Rats, monkeys, and humans can alter the size of their spinal stretch reflex and its electrically induced analog, the H-reflex (HR), when exposed to an operant conditioning paradigm. Because this conditioning induces plasticity in the spinal cord, it offers a unique opportunity to identify the neuronal sites and mechanisms that underlie a well-defined change in a simple behavior. To facilitate these studies, we developed an HR operant conditioning protocol in mice, which are better suited to genetic manipulation and electrophysiological spinal cord study in vitro than rats or primates. Eleven mice under deep surgical anesthesia were implanted with tibial nerve stimulating electrodes and soleus and gastrocnemius intramuscular electrodes for recording ongoing and stimulus-evoked EMG activity. During the 24-h/day computer-controlled experiment, mice received a liquid reward for either increasing (up-conditioning) or decreasing (down-conditioning) HR amplitude while maintaining target levels of ongoing EMG and directly evoked EMG (M-responses). After 3-7 wk of conditioning, the HR amplitude was 133 +/- 7% (SE) of control for up-conditioning and 71 +/- 8% of control for down-conditioning. HR conditioning was successful (i.e., > or =20% change in HR amplitude in the appropriate direction) in five of six up-conditioned animals (mean final HR amplitude = 139 +/- 5% of control HR for successful mice) and in four of five down-conditioned animals (mean final HR amplitude = 63 +/- 8% of control HR for successful mice). These effects were not attributable to differences in the net level of motoneuron pool excitation, stimulation strength, or distribution of HR trials throughout the day. Thus mice exhibit HR operant conditioning comparable with that observed in rats and monkeys.
Keywords: Spinal Cord

Modulation in spinal circuits and corticospinal connections following nerve stimulation and operant conditioning. - Thompson, Aiko K.; Stein, Richard B.; Xiang Yang Chen; Jonathan Wolpaw (Conference proceedings : ... Annual International Conference of the IEEE Engineering in Medicine and Biology Society. IEEE Engineering in Medicine and Biology Society. Conference, 2006)
Neural plasticity occurs throughout adult life. In healthy individuals, different spinal pathways are differently modulated during different daily activities. Drastic changes to nervous system activity and connections caused by injuries or diseases alter spinal reflexes, and this is often related to disturbed motor functions. In both health and disease, spinal reflexes are subject to substantial modifications. Plasticity in supraspinal descending connections is even more remarkable; corticospinal connectivity has been shown to be extremely plastic. In this session, we describe two approaches for possibly improving recovery after central nervous system (CNS) lesions. They are very different, but both involve repetitive nerve stimulation and CNS plasticity. The first approach is functional electrical stimulation (FES) of the common peroneal nerve, which has been used to treat foot drop in patients with CNS lesions. The second approach is operant conditioning of a spinal reflex. Spinal reflex operant conditioning studies in animal models have shown plastic changes in spinal cord neurons associated with this form of learning and improved locomotor function in incomplete spinal cord injured rats. Thus, reflex conditioning might be a robust approach to inducing plasticity at spinal and supraspinal levels. As a first step in establishing this approach and characterizing its effects in the human adult CNS, we are currently investigating the extent and time course of operant conditioning of the soleus H-reflex in healthy subjects. In results to date, all subjects (n=5) have changed reflex size in the correct direction to various degree (16-36%) over 2-3 months of conditioning, indicating possibility that H-reflex conditioning can occur in humans. At the same time, the substantial inter-subject variation in the time course and extent of conditioning suggest that additional data are needed to establish its principal features. We hope that studying modulation and modification o- f the CNS by different approaches will help us further understand the plasticity of the human adult nervous system.
Keywords: Spinal Cord

Motor learning changes GABAergic terminals on spinal motoneurons in normal rats. - Wang, Yu; Pillai, Shreejith; Jonathan Wolpaw; Xiang Yang Chen (The European journal of neuroscience, 2006)
The role of spinal cord plasticity in motor learning is largely unknown. This study explored the effects of H-reflex operant conditioning, a simple model of motor learning, on GABAergic input to spinal motoneurons in rats. Soleus motoneurons were labeled by retrograde transport of a fluorescent tracer and GABAergic terminals on them were identified by glutamic acid decarboxylase (GAD)67 immunoreactivity. Three groups were studied: (i) rats in which down-conditioning had reduced the H-reflex (successful HRdown rats); (ii) rats in which down-conditioning had not reduced the H-reflex (unsuccessful HRdown rats) and (iii) unconditioned (naive) rats. The number, size and GAD density of GABAergic terminals, and their coverage of the motoneuron, were significantly greater in successful HRdown rats than in unsuccessful HRdown or naive rats. It is likely that these differences are due to modifications in terminals from spinal interneurons in lamina VI-VII and that the increased terminal number, size, GAD density and coverage in successful HRdown rats reflect and convey a corticospinal tract influence that changes motoneuron firing threshold and thereby decreases the H-reflex. GABAergic terminals in spinal cord change after spinal cord transection. The present results demonstrate that such spinal cord plasticity also occurs in intact rats in the course of motor learning and suggest that this plasticity contributes to skill acquisition.
Keywords: activity-dependent plasticity; GABA; H-Reflex; Memory; Motor control; Spinal Cord

Long-term spinal reflex studies in awake behaving mice. - Jonathan S. Carp; Tennissen, Ann M.; Xiang Yang Chen; Gerwin Schalk; Jonathan Wolpaw (Journal of neuroscience methods, 2005)
The increasing availability of genetic variants of mice has facilitated studies of the roles of specific molecules in specific behaviors. The contributions of such studies could be strengthened and extended by correlation with detailed information on the patterns of motor commands throughout the course of specific behaviors in freely moving animals. Previously reported methodologies for long-term recording of electromyographic activity (EMG) in mice using implanted electrodes were designed for intermittent, but not continuous operation. This report describes the fabrication, implantation, and utilization of fine wire electrodes for continuous long-term recordings of spontaneous and nerve-evoked EMG in mice. Six mice were implanted with a tibial nerve cuff electrode and EMG electrodes in soleus and gastrocnemius muscles. Wires exited through a skin button and traveled through an armored cable to an electrical commutator. In mice implanted for 59-144 days, ongoing EMG was monitored continuously (i.e., 24 h/day, 7 days/week) by computer for 18-92 days (total intermittent recording for 25-130 days). When the ongoing EMG criteria were met, the computer applied the nerve stimulus, recorded the evoked EMG response, and determined the size of the M-response (MR) and the H-reflex (HR). It continually adjusted stimulation intensity to maintain a stable MR size. Stable recordings of ongoing EMG, MR, and HR were obtained typically 3 weeks after implantation. This study demonstrates the feasibility of long-term continuous EMG recordings in mice for addressing a variety of neurophysiological and behavioral issues.
Keywords: Electromyography; implanted electrodes; Monosynaptic; Spinal Cord

Operant conditioning of rat H-reflex affects motoneuron axonal conduction velocity. - Jonathan S. Carp; Xiang Yang Chen; Sheikh, H.; Jonathan Wolpaw (Experimental brain research. Experimentelle Hirnforschung. Expérimentation cérébrale, 2001)
This study assessed the effects of operant conditioning of the H-reflex on motoneuron axonal conduction velocity in the rat. After measurement of the control H-reflex size, rats were either exposed for at least 40 days to the HRup or HRdown conditioning mode, in which reward occurred only if the soleus H-reflex was greater than (HRup mode) or less than (HRdown mode) a criterion or continued under the control condition (HRcon mode) in which the H-reflex was simply measured. We then measured axonal conduction velocity of triceps surae motor units of HRup, HRdown, and HRcon rats by stimulating the axon in the ventral root and recording from the tibial nerve. Conduction velocity was 8% less in successful HRdown rats than in HRcon rats (P=0.02). Conduction velocity in HRup rats and unsuccessful HRdown rats was not significantly different from that in HRcon rats. Since recording bypassed the intra-spinal portion of the motoneuron, the change was clearly in the axon. This decrease was similar to the 6% decrease previously found in successful HRdown monkeys. Unsuccessful HRdown rats and monkeys did not show this decrease. This result suggests that the mechanism of HRdown conditioning is similar in rats and monkeys and provides further support for the hypothesis that HRdown conditioning decreases motoneuron excitability by producing a positive shift in firing threshold. While traditional theories of learning emphasize synaptic plasticity, neuronal plasticity may also contribute to operantly conditioned behavioral changes.
Keywords: conduction velocity; H-Reflex; motoneuron; plasticity; Spinal Cord

Operant conditioning of rat H-reflex: effects on mean latency and duration. - Jonathan Wolpaw; Xiang Yang Chen (Experimental brain research. Experimentelle Hirnforschung. Expérimentation cérébrale, 2001)
We are currently studying the mechanisms of operantly conditioned changes in the H-reflex in the rat. Primate data suggest that H-reflex decrease is due to a positive shift in motoneuron firing threshold and a small decrease in the monosynaptic excitatory postsynaptic potential (EPSP), and that increase might be due to change in group-I oligosynaptic (especially disynaptic) input. To further evaluate the possibility of conditioned change in oligosynaptic input, we compared the mean latency (i.e., the average latency of the entire H-reflex) and the duration of control (i.e., pre-conditioning) H-reflexes with those of H-reflexes after up-conditioning or down-conditioning. Up-conditioning was associated with small, statistically significant increases in H-reflex mean latency [+0.11+/-0.05 (+/-SE) ms] and duration (+0.32+/-0.16 ms). The mean latency of the H-reflex increase (i.e., the part added to the H-reflex by up-conditioning) was 0.28+/-0.14 (+/-SE) ms greater than that of the control H-reflex. Down-conditioning had no significant effect on mean latency or duration. While these results indicate that operant conditioning does not greatly change H-reflex mean latency or duration, the effects detected with up-conditioning are consistent with the hypothesis that decreased inhibition, or increased excitation, by homonymous and heteronymous group-I oligosynaptic input contributes to the H-reflex increase produced by up-conditioning. Several other mechanisms might also account for these small effects.
Keywords: conditioning; H-Reflex; Memory; plasticity; Spinal Cord

Time course of H-reflex conditioning in the rat. - Xiang Yang Chen; Lu Chen; Jonathan Wolpaw (Neuroscience letters, 2001)
This study sought to define the course of operantly conditioned change in the rat soleus H-reflex and to determine whether, like H-reflex conditioning and spinal stretch reflex conditioning in the monkey, it develops in distinct phases. Data from 33 rats in which the right soleus H-reflex was trained up (i.e. HRup mode) and 38 in which it was trained down (i.e. HRdown mode) were averaged to define the courses of H-reflex increase and decrease. In HRup rats, the H-reflex showed a large phase I increase within the first 2 days followed by gradual phase II increase that continued for weeks. In HRdown rats, the H-reflex appeared to show a small phase I decrease and then showed a gradual phase II decrease over weeks. In combination with other recent work, the data suggest that H-reflex conditioning begins with a rapid mode-appropriate alteration in corticospinal tract influence over the spinal arc of the H-reflex, which causes phase I change, and that the continuation of this altered influence induces gradual spinal cord plasticity that is responsible for phase II change. The results further establish the similarity of H-reflex conditioning in primates and rats. Thus, they encourage efforts to produce a single coherent model of the phenomenon based on data from the two species and indicate the potential clinical relevance of the rat data.
Keywords: conditioning; Learning; Memory; plasticity; rat; Reflex; Spinal Cord

Dorsal column but not lateral column transection prevents down-conditioning of H reflex in rats. - Xiang Yang Chen; Jonathan Wolpaw (Journal of neurophysiology, 1997)
Operant conditioning of the H reflex, the electrical analogue of the spinal stretch reflex, in freely moving rats is a relatively simple model for studying long-term supraspinal control over spinal cord function. Motivated by food reward, rats can gradually increase or decrease the soleus H reflex. This study is the first effort to determine which spinal cord pathways convey the descending influence from supraspinal structures that changes the H reflex. In anesthetized Sprague-Dawley rats, the entire dorsal column (DC), which includes the main corticospinal tract, or the right lateral column (LC) was transected by electrocautery. Animals recovered quickly and the minimal transient effects of transection on the right soleus H reflex disappeared within 16 days. Beginning at least 18 days after transection, 12 rats were exposed to the HRdown-conditioning mode, in which reward was given when the H reflex of the right soleus muscle was below a criterion value. In seven LC rats exposed to the HRdown mode, the H reflex fell to 71 +/- 8% (mean +/- SE) of its initial value. In six of the seven, conditioning was successful (i.e., decrease to < or = 80%). These results were comparable with those previously obtained from normal rats. In contrast, in five DC rats exposed to the HRdown mode, the H reflex at the end of exposure was 106 +/- 12% of its initial value. In none of these rats was HRdown-conditioning successful. DC rats differed significantly from normal and LC rats in both final H reflex values and number successful. In five DC and three LC rats that continued under control conditions over 30-78 days, the H reflex at the end of the period was 98 +/- 4% and 100 +/- 8%, respectively, of its initial value, indicating that DC or LC transection itself did not lead to gradual increase or decrease in the H reflex. The results indicate that the DC, containing the main corticospinal tract, is essential for HRdown-conditioning, whereas the ipsilateral LC, containing the main rubrospinal, vestibulospinal, and reticulospinal tracts, is not essential. Combined with the known muscular specificity of conditioning, these results suggest that the main corticospinal tract is essential for HRdown-conditioning. The DC ascending tract might also be necessary. The respective roles of the DC descending and ascending tracts, and transection effects on HRup-conditioning and on the maintenance of both HRup- and HRdown-conditioning after they have occurred, remain to be defined.
Keywords: Spinal Cord

Reversal of H-reflex operant conditioning in the rat. - Xiang Yang Chen; Jonathan Wolpaw (Experimental brain research. Experimentelle Hirnforschung. Expérimentation cérébrale, 1996)
In response to an operant conditioning task, rats can gradually increase or decrease soleus H-reflex amplitude without change in background electromyographic activity or M response amplitude. Both increase (under the HRup mode) and decrease (under the HRdown mode) develop over weeks. The present study investigated reversal of conditioned H-reflex change. Following collection of control data, rats were exposed to one mode (HRup or HRdown) for 50 days, and then exposed to the opposite mode for up to 72 days. Rats responded to each mode exposure with gradual, mode-appropriate change in H-reflex amplitude. This finding is consistent with other evidence that H-reflex conditioning depends on spinal cord plasticity. The effects of exposure to the HRup (or HRdown) mode were not affected by whether exposure followed previous exposure to the HRdown (or HRup) mode. In accord with recent studies suggesting that HRup and HRdown conditioning have different spinal mechanisms, these results suggest that reversal of H-reflex change is due primarily to the superimposition of additional plasticity rather than to decay of the plasticity responsible for the initial change.
Keywords: H-Reflex; operant conditioning; plasticity; rat; soleus muscle; Spinal Cord

Operant conditioning of H-reflex in freely moving rats. - Xiang Yang Chen; Jonathan Wolpaw (Journal of neurophysiology, 1995)
1. Primates can increase or decrease the spinal stretch reflex and its electrical analogue, the H-reflex (HR), in response to an operant conditioning task. This conditioning changes the spinal cord itself and thereby provides an experimental model for defining the processes and substrates of a learned change in behavior. Because the phenomenon has been demonstrated only in primates, its generality and theoretical implications remain unclear, and its experimental use is restricted by the difficulties of primate research. In response to these issues, the present study explored operant conditioning of the H-reflex in the rat. 2. Seventeen Sprague-Dawley rats implanted with chronic electromyographic (EMG) recording electrodes in one soleus muscle and nerve cuff stimulating electrodes on the posterior tibial nerve were rewarded (either with medial forebrain bundle stimulation or food) for increasing (HRup conditioning mode) or decreasing (HRdown conditioning mode) soleus H-reflex amplitude without change in background EMG or M response (direct muscle response) amplitude. 3. H-reflex amplitude changed appropriately over 3-4 wk. Under the HRup mode, it rose to an average of 158 +/- 54% (mean +/- SD) of initial value, whereas under the HRdown mode it fell to an average of 67 +/- 11% of initial value. Background EMG and M response amplitude did not change. 4. Operant conditioning of the H-reflex in the rat appears similar in rate and final magnitude of change to that observed in the monkey.(ABSTRACT TRUNCATED AT 250 WORDS)
Keywords: Spinal Cord

Triceps surae motoneuron morphology in the rat: a quantitative light microscopic study. - Xiang Yang Chen; Jonathan Wolpaw (The Journal of comparative neurology, 1994)
The rat is now the model of choice for many studies of motor function. However, little quantitative information on the structure of rat motoneurons is available. In conjunction with efforts to define the physiologic and anatomic substrates of operantly conditioned plasticity in the spinal cord, 13 physiologically identified triceps surae motoneurons in the rat lumbar spinal cord were labeled intracellularly with horseradish peroxidase and completely reconstructed and measured with a computer-based neuron-tracing system. Somata were all located in the ventral horn of lumbar segments 4-5, had an average diameter of 35 microns, and had 6-12 dendrites. Dendrites ramified throughout the ventral horn and also penetrated the white matter. Their spread was greater in the rostrocaudal and dorsoventral directions (1.53 +/- 0.24 mm and 1.35 +/- 0.23 mm, respectively) than in the mediolateral direction (0.85 +/- 0.14 mm). Regardless of soma location, dendritic fields usually extended throughout the ipsilateral coronal cross-section of the ventral horn. As a result, the ventral or lateral extent of the field was correlated strongly with the soma's distance from the ventral or lateral border, respectively, of the ventral horn. Furthermore, although soma locations in the coronal plane varied widely, the centers of the dendritic fields tended to cluster near the center of the ventral horn. Dendrites constituted 96.2-98.4% (mean +/- SD = 97.3 +/- 0.7%) of the total neuronal surface area. Each of the 104 dendrites studied had an average of 13 branch points and 27 segments. First-order segment diameters ranged from 1.4 to 11.7 microns (mean +/- SD = 5.3 +/- 2.1 microns). Total dendritic length, surface area, volume, number of dendritic segments, and maximum segment order were correlated strongly with diameter of the first-order segment. Proceeding distally between branch points, the mean decrease in dendritic diameter (i.e., tapering) +/- the standard deviation was 22 +/- 8% of the proximal diameter. The average ratio +/- the standard deviation of the sum of the average diameters of each daughter segment raised to the 1.5 power to the average diameter of the parent segment raised to the 1.5 power (i.e., Rall's ratio; Rall, 1959) was 0.87 +/- 0.08. In comparison with cat alpha-motoneurons, rat motoneurons had smaller soma diameters, fewer dendrites, smaller total surface areas, and shorter total dendritic lengths. However, the number of terminations per dendrite was similar in the two species, so that rat motoneurons had more terminations per unit dendritic length.(ABSTRACT TRUNCATED AT 400 WORDS)
Keywords: computer assisted; dendrites; horseradish peroxidase; image processing; Software; Spinal Cord